The Effect of the Dollar, Euro, and Sterling Exchange on the Tourism Index in the Turkish Economy - AHMADOV, Fariz; HUSEYNLI, Nigar; HUSEYNLI, Bahman (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023, 2023)
The exchange rate expresses the value of the national currency in terms of foreign currency. While foreign currency is an important investment tool in the portfolio of all kinds of investors in our modern world, it is also one of the most important elements of international trade. In particular, the impact of exchange rates on the tourism sector cannot be ignored. The aim of this study is to examine the relationship between monthly data and BIST tourism index (XTRZM) for the period January 2011 – July 2022 and exchange rates (US Dollar exchange rate, Euro exchange rate and Sterling exchange rate) by using the time series process. Whether there is a relationship between the variables was analyzed by econometric analysis method. In the study, in which the Granger model was applied, it was determined that there was a causal relationship between all four variables. A bidirectional relationship was found only between dollar and sterling exchange rate changes. A unilateral causality relationship was found between all other variables.